Computational analysis revealed miRNAs produced by Chikungunya virus target genes associated with antiviral immune responses and cell cycle regulation. (June 2021) - Islam, Md. Sajedul; Khan, Md. Abdullah-Al-Kamran
Graphical abstract: Highlights: An in silico analysis that predicts miRNAs of Chikungunya virus (CHIKV). Genes targeted by miRNAs are associated with antiviral immune response and cellular proliferation. Altered expression of genes that modulate cell cycle. Abstract: Chikungunya virus (CHIKV) that causes chikungunya fever, is an alphavirus that belongs to the Togaviridae family containing a single-stranded RNA genome. Mosquitoes of the Aedes species act as the vectors for this virus and can be found in the blood, which can be passed from an infected person to a mosquito through mosquito bites. CHIKV has drawn much attention recently because of its potential of causing an epidemic. As the detailed mechanism of its pathogenesis inside the host system is still lacking, in this in silico research we have hypothesized that CHIKV might create miRNAs, which would target the genes associated with host cellular regulatory pathways, thereby providing the virus with prolonged refuge. Using bioinformatics approaches we found several putative miRNAs produced by CHIKV. Then we predicted the genes of the host targeted by these miRNAs. Functional enrichment analysis of these targeted genes shows the involvement of several biological pathways regulating antiviral immune stimulation, cellular proliferation, and cell cycle, thereby provide themselves with prolonged refuge and facilitate their pathogenesis, which in turn may lead to disease conditions. Finally, we analyzed a publicly available microarray dataset (GSE49985) to determine the altered expression levels of the targeted genes and found genes associated with pathways such as cell differentiation, phagocytosis, T-cell activation, response to cytokine, autophagy, Toll-like receptor signaling, RIG-I like receptor signaling and apoptosis. Our finding presents novel miRNAs and their targeted genes, which upon experimental validation could facilitate in developing new therapeutics to combat CHIKV infection and minimize CHIKV mediated diseases.